PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP NYERI PERSALINAN KALA I FASE AKTIF DI RUANG VK RSUD TEBING TINGGI KAB. EMPAT LAWANG - Yuni Ramadhaniati; Ruri Maiseptya Sari; Diana Sari (Journal Prima Health Science, 2020)
Labor pain can be controlled by two methods, pharmacological and non-pharmacologicaL. In the nonpharmacolgismethod there are various methods, one of which is deep breathing relaxation techniques.The purpose of this study was todetermine the effect of deep breathing relaxation techniques on labor pain in the first phase of the active phase in VKTebing Tinggi Regional General Hospital, Empat Lawang Regency. This study used a Pre-Experimental Pretest-PosttestDesign method and the sample was taken by accidental sampling with a total sample of 35 respondents. Analisis yangdigunakan adalah analisis univariat dan bivariat menggunakan uji Wilcoxon. The results of the study showed that of 35respondents, before breathing relaxation techniques were done in there were severe pain of 11.4% and moderate pain in88.6% whereas after breathing relaxation techniques in light pain there were 62, 9% and moderate pain in 37.1%. Basedon the results of the study there is the effect of deep breathing relaxation techniques on labor pain in the first phase ofthe active phase as evidenced by the Wilcoxon statistical test value of Z = -5.245 with a p value of 0.000 <0.05 whichmeans that Ha is accepted. It is expected that the results of this study midwives can provide the best service and play anactive role in applying deep breathing relaxation techniques in first-phase maternal mothers in the active phase of VKHospital inebing Tinggi, Kab. Empat Lawang.